Analisis Dampak Ketidakpahaman Nasabah terhadap Akad Syariah dalam Produk Tabungan Haji dan Umroh - Kurniawan, Taufiq (DPPM Universitas Pelita Bangsa, 2025)
The existence of a contract is a very important matter in a transaction according to Islamic economic law. This contract is valid if all the pillars and conditions of the contract are fulfilled. Many Indonesian Muslims want to perform the hajj pilgrimage but do not have enough funds. Therefore, BPRS Harta Insan Karimah Bekasi introduced a hajj and umrah savings product with the mudarabah concept, namely that customers can only withdraw their savings if they have reached the minimum amount to perform the hajj pilgrimage. This study was conducted to determine how customers understand the contracts that have been used in this product. Data collection was carried out by interviewing BPRS HIK Bekasi and customers who save on the product. This study found that in general, customers do not fully understand the nature of the contracts used in hajj and umrah savings products. They are also not ready to bear the risk of loss from the management of their funds. In practice, BPRS HIK Bekasi provides voluntary security guarantees for mudarabah capital. Although in a mudarabah agreement, capital funds cannot be guaranteed against losses, there are opinions that allow this if done voluntarily.